Differential method to determine thermal degradation kinetics of chlorophyll in virgin olive oil - AHMET LEVENT INANC (Italian Journal of Food Science, 2016)
Differential method is presented to study thermal degradation kinetics of chlorophyll in virgin olive oil. The oil samples, naturally containing 20.0 mg/kg chlorophyll were stored at 150°, 160°, 170°, 180°, 190° and 200°C until the time at which chlorophyll contents had reduced to the certain amounts. The concentration gradually decreased as heating time increased. A half order equation was found as the best model for the present experimental data. Differential method with graphic and substitution methods was compared for the determination of the rate constant and the half-time. The rate constants and half life at 150°C were  determined in the range of 0.20-0.22 and 12.14-13.12 for the thermal process of chlorophyll in virgin olive oil, respectively. The reaction rates increased approximately 1.1 times with increment of every 10°C from temperature of 150°C. Conversely, the half lifes decreased 0.9 times for increment of every 10°C. The activation energies were approximately 24 J/kg for differential method, and 22 J/kg for graphic and substitution methods.